New cases of rare dyslipidemias in clinical practice - Rodríguez-Jiménez, C; Sanguino, J; Sevilla-Alonso, E; Arrieta, F; García-Polo, I; Mostaza, JM; Rodríguez-Nóvoa, S (Journal of Cardiovascular Medicine and Cardiology, 2022)
Lipid metabolism can experience different disorders resulting in changes in the function and concentrations of plasma lipoproteins. These changes affect alone or interact with other cardiovascular risk factors involved in the development of atherosclerosis. Therefore, dyslipidemias cover a wide spectrum of disorders lipids. Some of them have a genetic origin and very low prevalence. The main objective of this article is to report new cases of rare dislipemias of genetic origin in our population. Genetic analysis was performed by Next Generation Sequencing (NGS) using a customized panel of 436 genes in DNA samples of four patients. The results confirmed the genetic origin of the following dyslipidemias: fish-eye disease, primary hypoalphalipoproteinemia-2, familial hypercholesterolemia by a variant in STAP1 and Sitosterolemia. This approach allows us to confirm the genetic diagnosis of four patients with alterations in lipid metabolism, this will help to improve patient management, achieving early diagnosis in the study of family members.